Assessment of polyaniline nanoparticles toxicity and teratogenicity in aquatic environment using Rhinella arenarum model - Ibarra, Luis Exequiel (2015)
With the rapid growth of nanotechnology and the applications of nanoparticles, environmental exposure to these particles is increasing. However, their impact in human and environmental health is not well studied. Anurans, with life stage comprising embryos, tadpoles and adults, have an extremely permeable skin which makes them excellent indicators of environmental health. This study evaluated the acute toxicity effects of polyaniline nanoparticles (PANI-Np) in different dispersant on embryos and larvae of Rhinella arenarum. The results showed that LC50 of PANI-Np dispersed in polyvinylpyrrolidone (PVP) were 1500mg/L, while LC50 by PANI-Np dispersed in PVP+PNIPAM (polyN-isopropylacrilamide) showed a highest toxicity (1170mg/L). The embryo teratogenicity increased with increasing exposure concentration in both kinds of PANI-Np although in PANI-Np1, there is an increased teratogenic effect associated with the polymer stabilizer PVP.